Corpus callosotomy versus vagus nerve stimulation for atonic seizures and drop attacks: A systematic review - Rolston, John D. (Epilepsy Behav, 2015)
Atonic seizures are debilitating and poorly controlled with antiepileptic medications. Two surgical options are primarily used to treat medically refractory atonic seizures: corpus callosotomy (CC) and vagus nerve stimulation (VNS). However, given the uncertainty regarding relative efficacy and surgical complications, the best approach for affected patients is unclear. The PubMed database was queried for all articles describing the treatment of atonic seizures and drop attacks with either corpus callosotomy or VNS. Rates of seizure freedom, >50% reduction in seizure frequency, and complications were compared across the two patient groups. Patients were significantly more likely to achieve a >50% reduction in seizure frequency with CC versus VNS (85.6% versus 57.6%; RR: 1.5; 95% CI: 1.1–2.1). Adverse events were more common with VNS, though typically mild (e.g., 22% hoarseness and voice changes), compared with CC, where the most common complication was the disconnection syndrome (13.2%). Both CC and VNS are well tolerated for the treatment of refractory atonic seizures. Existing studies suggest that CC is potentially more effective than VNS in reducing seizure frequency, though a direct study comparing these techniques is required before a definitive conclusion can be reached.